Peculiarities of pregnancy development and condition of fetus in pregnant women diagnosed with gestational and chronic pyelonephritis - Gaystruk, N. A.; Suprunova, T. V.; Nadezhdin, M. V.; Ponina, S. I. (Journal of Education, Health and Sport, 2017)
Gaystruk N. A., Suprunova T. V., Nadezhdin M. V., Ponina S. I. Peculiarities of pregnancy development and condition of fetus in pregnant women diagnosed with gestational and chronic pyelonephritis. Journal of Education, Health and Sport. 2017;7(1):423-436. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.292938 http://ojs.ukw.edu.pl/index.php/johs/article/view/4272 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDK 618.36;618.3-16,155.194.5.021 PECULIARITIES OF PREGNANCY DEVELOPMENT AND CONDITION OF FETUS IN PREGNANT WOMEN DIAGNOSED WITH GESTATIONAL AND CHRONIC PYELONEPHRITIS N. A. Gaystruk, T. V. Suprunova, M. V. Nadezhdin, S. I. Ponina N. I. Pirogov <a href="https://www.google.com.ua/url?sa=t&rct=j&q=&esrc=s&source=web&cd=4&ved=0ahUKEwiRiN7Rg5zQAhVLWCwKHX2XDwYQFgg2MAM&url=http%3A%2F%2Fwww.esska.org%2Fteaching-centres%2Fesska-accredited-teaching-centres%2Fteaching-centre-detail%3Fteaching_id%3D137&usg=AFQjCNFsZpQu2lfJvF-bFDcjEHjwMZ46DQ" target="_blank">Vinnitsa National Medical University, Vinnitsa Summary The article presents the data of the study of basically healthy pregnant women and pregnant women diagnosed with gestational and chronic pyelonephritis. There was carried out the analysis of pregnancy development and complications, delivery and post-delivery period, as well as the condition of fetus on the basis of the data of the bio-physical profile of fetus, cardiotocographic study and dopplerometric indicators of the bloodstream in uterine arteries and arteries of the navel-cord.Pregnant women with gestational pyelonephritis, compared to healthy pregnant women, more often experience such complications in pregnancy as light and moderate degree of preeclampsia, threatened miscarriage, anemia of pregnancy, placenta dysfunction. In accordance with the data of cardiotocography and bio-physical profile, disorder in the condition of fetus is observed, and resistance in the vessels of feto-placental system enhances. The mentioned above complications in conditions of chronic pyelonephritis are of a much larger-scale being compared with the ones in conditions of gestational pyelonephritis. Key words: gestational and chronic pyelonephritis in pregnancy, bio-physical profile of fetus, cardiotocographic study, dopplerometric indicators of bloodstream